Coral Bleaching Susceptibility Is Decreased following Short-Term (1–3 Year) Prior Temperature Exposure and Evolutionary History. (8th August 2011) - Haslun, Joshua A.; Strychar, Kevin B.; Buck, Gregory; Sammarco, Paul W.
Abstract : Coral exposed to short periods of temperature stress (≥1.0 ∘ C above mean monthly maximum) and/or increased frequencies of high temperatures may bolster resilience to global warming associated with climate change. We compared Montastraea cavernosa (Linnaeus, 1767; Cnidaria, Scleractinia, Faviidae) from the Florida Keys National Marine Sanctuary (FKNMS) and the Flower Garden Banks National Marine Sanctuary (FGBNMS). Thermal stress has been reported frequently within the FKNMS; however, corals in the FGBNMS experience nominal exposures to similar stressors. Corals were exposed to three temperatures (27 ∘ C, 31 ∘ C, and 35 ∘ C) for 72 h. Colonies from the FKNMS lost significantly fewer viable and necrotic zooxanthellae under conditions of acute stress (35 ∘ C) than the FGBNMS colonies. This indicates that the FKNMS corals are less temperature-sensitive than those in the FGBNMS. The observed differences point to greater prior temperature exposure and adaptation in the former versus the latter site when correlated to previous years of thermal exposure.